THE IMPORTANCE OF SUBMITTING MINI PLAN BEFORE TEACHING ENGLISH AS FOREIGN LANGUAGE AT INTENSIVE ENGLISH COURSE BEKASI BRANCHES - Abdulloh abdulloh (STIBA IEC JAKARTA, 2017)
This study aimed to determine the importance implementation of lesson plan” Mini Plan” to improve the competence of the perspective teacher of English at one of the English schools, IEC in Bekasi. The competence in this study referred to the competence of preparing lesson plan and implementing classroom practice using mini lesson plan . This research conducted on population of 30 teachers and sample of 7 teachers of English clasess in IEC Bekasi. This study was descriptive study. This study tells us the condition before the implementation of submitting mini plan and after that implementation.The result shows that the readyness, professioanalism, achievement of the teachers before teaching, and the students retention in class are increased.